2009
DOI: 10.1007/s12253-009-9206-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-radiotherapy in Locally Advanced Squamous Cell Oesophageal Cancer—are Upper Third Tumours more Responsive?

Abstract: Before neoadjuvant therapy was widely applied, the prognosis of oesophageal cancer had been considered dependent on the location of the tumor, i.e. upper third cancers had had the worst prognosis. The aim of this retrolective study was to prove the efficiency of the neoadjuvant treatment, and to compare the response of esophageal cancer in different locations. Between January 1998 and September 2005, 102 patients with locally advanced squamous cell oesophageal cancer received preoperative chemo-radiotherapy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
8
0
4
Order By: Relevance
“…Papp et al once compared the effect of 4-week-long preoperative chemoradiotherapy between 40 cases of upper-third ESCC and 62 cases of middle-third ESCC. In the end, complete remission was achieved in 35% (14/40) of the former group but in only 4.8% (3/62) of the latter group (P <0.05), suggesting a sitespecifically different tumor biology (14).…”
Section: Discussionmentioning
confidence: 91%
“…Papp et al once compared the effect of 4-week-long preoperative chemoradiotherapy between 40 cases of upper-third ESCC and 62 cases of middle-third ESCC. In the end, complete remission was achieved in 35% (14/40) of the former group but in only 4.8% (3/62) of the latter group (P <0.05), suggesting a sitespecifically different tumor biology (14).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, surgery may play a role in the salvage treatment of patients who were defined nonresponders to induction therapy, but in patients who were defined as responders, surgery can no longer be recommended as a routine treatment. If there is no evidence of residual disease or stricture at the pharyngo-esophageal junction, the patient can be closely followed and surgery may be avoided [18,19]. Our prospective clinical study examined the effects of chemoradiotherapy on postoperative organ function, inflammatory response and the nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment modalities for upper ESCC are mainly radiotherapy, surgery, or radiotherapy in combination with surgery. In addition, some studies have shown that concurrent chemoradiotherapy was effective against upper third ESCC [ 11 , 12 ], or that upper third EC was especially sensitive to preoperative chemoradiotherapy, which significantly improved survival [ 13 ]. Surgery has even been demonstrated recently as better than radiotherapy for therapeutic effect in upper third ESCC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%